Decreased frequency of the HLA- DRB1*11 allele in patients with chronic hepatitis C virus infection - Yenigün A.; Durupinar B. (My University, 2001)
Backrounds/Aims: A genetically determined resistance or susceptibility to chronic hepatitis C virus infection (HCV) may make an important contribution to the course of liver disease and may be linked to the human major histocompatibility complex. The aim of this study was to investigate the HLA-Class II genotype profile in Chronic Hepatitis C and HLA- hepatitis C association. Methods: The series were composed of 49 unrelated patients (31 females. 18 males; mean age at onset= 54.4±1.7 years; range 34-73 year). The control population consisted of 43 ethnically-matched healthy donors. HLA-DR and -DQ alleles were studied in patients and controls by Polymerase Chain Reaction- Sequence Specific Primer (PCR-SSP) low resolution method. Anti-HCV was investigated with ELISA II and HCV-RNA with reverse transcriptase "nested" PCR. Results: Two HLA class II alleles, DRB1*11,and DRB5 were present at a significantly lower frequency in 49 patients with chronic hepatitis C (anti- HCV and HCV-RNA positive) compared with controls (22,4% vs. 14.3%, and 51,2% vs. 32.6%, respectively) though only DR*11 was significant (p< 0.05, OR= 0.3, with 95% confidence interval [CI] of 0.1 to 0.7). No further HLA associations with chronic HCV infection were observed and there was no correlation between stage of disease Conclusions: In conclusion, these findings suggest that HLA-DRB1*11 may have a protective feature to Chronic HCV infection. © 2001 Blackwell Science Ltd,.